Applying the Kessler Foundation Modified Story Memory Technique to Improve New Learning in Aging Populations - Nancy D. Chiaravalloti; Erica Weber; Silvana L. Costa; Jean Lengenfelder; Diana Maloku; Nancy B. Moore; John DeLuca (Dementia and Geriatric Cognitive Disorders Extra)
Introduction: The current study examined the efficacy of the 10-session Kessler Foundation modified Story Memory Technique (KF-mSMT®) to improve new learning in older adults. Methods: This double-blind, placebo-controlled randomized clinical trial included twenty-eight individuals over age 65 randomized to the treatment group (n = 17) or placebo control group (n = 13). Participants completed a baseline neuropsychological assessment, including questionnaires assessing everyday memory, and a repeat assessment immediately post-treatment. The primary outcome measure was the total learning score from the California Verbal Learning Test II (CVLT-II) and the secondary outcome measure was the total score from the Memory Functioning Questionnaire. Results: A significant effect of the KF-mSMT® was noted on the CVLT-II total learning score in the treatment group, demonstrating a large effect size. Post hoc analysis examining benefit from the KF-mSMT® in the healthy aging group as compared with the mild cognitive impairment (MCI) group showed a trend toward significance (p = 0.069), with a large effect size. With benefit defined as a 10% or greater improvement in the CVLT total learning, 65% of patients in the treatment group showed improvement from baseline to immediate follow-up, compared with 31% of the control group (p = 0.06). Significant treatment effects were also noted in a self-report measure of memory in daily life, the Memory Functioning Questionnaire. Post-treatment changes in depression or anxiety from before to after treatment were not significant between the groups. Conclusion: The current study presents preliminary evidence in support of the KF-mSMT® for improving learning and memory abilities in older populations of those aging normally and those meeting criteria for MCI.